Pengaruh Pemberian Abu Sekam Padi terhadap Pertumbuhan Dan Hasil Tanaman Cabe Rawit (Capsicum frutescents L.) pada Tanah Rawa Lebak - Norhasanah Norhasanah; Nira Yusnita (Rawa Sains: Jurnal Sains STIPER Amuntai, 2011)
Lebak wetland is potential for cultivation of various types of vegetables, especially cayenne pepper. The problem in the land is an increase in the solubility of Al, Fe, Mn, and Cu which can poison plants. To overcome this problem, the effort that can be done is to provide organic material. This study aims to (i) determine the effect of dosages of rice husk ash on the growth and yield of cayenne in swamp lebak, (ii) obtain the best dosage of rice husk ash for growth and yield of cayenne pepper in swampy swampy soil. The study was conducted in Palampitan Hilir Village, Amuntai Tengah District, Hulu Sungai Utara Regency, from March - May 2010, this study used a Randomized Block Design (RBD), with 5 treatments and 4 replications, so that 20 experimental units were obtained, and 4 treatments. The factors tested were doses of rice husk ash, namely: p0 = 0 g. polybag -1, p1 = 24 g. polybag -1, p2 = 48 g. polybag -1, p3 = 72 g. polybag-1, and p4 = 96 g. polybag -1. The results showed that the treatment had a very significant effect on all plant variables observed with the best dose of rice husk ash for vegetative growth was p2 and that generative growth was p3.